Performance Comparison of a QoS Aware Routing Protocol for Wireless Sensor Networks - Bhuyan, Bhaskar; Sarma, Nityananda (Scientific Research Publishing, 2016)
Quality of Service (QoS) in Wireless Sensor Networks (WSNs) is a challenging area of research because of the limited availability of resources in WSNs. The resources in WSNs are processing power, memory, bandwidth, energy, communication capacity, etc. Delay is an important QoS parameter for delivery of delay sensitive data in a time constraint sensor network environment. In this paper, an extended version of a delay aware routing protocol for WSNs is presented along with its performance comparison with different deployment scenarios of sensor nodes, taking IEEE802.15.4 as the underlying MAC protocol. The performance evaluation of the protocol is done by simulation using ns-2 simulator.
Keywords: Wireless Sensor Networks; Quality of Service; Delay; Time Constraint